Antiracism as daily practice : refuse shame, change white communities, and help create a just world - Harvey, Jennifer, 1971- (St. Martin's Press, 2024)
"Inspirational and wise, a step by step guide for white Americans to combat racism in their communities. Antiracism as Daily Practice illustrates the many ways white Americans--those newly waking to the crisis of racism in 2020 and those already aware--can choose behaviors in our everyday lives to grow racial justice. Full of real life stories, this book shows how vital it is for white people to engage in and with our families, through our social networks, in our neighborhoods, and at our jobs to make antiracism a daily living commitment. We have real power in our relationships with other white people--and not enough of us have used it. Dr. Harvey explains why we white people struggle with knowing what to do about racism, and explores the significance of emotions like grief and anger (as well as the harmful role of shame) in really reckoning with the transformation and change needed in our communities to become the partners in justice that Black communities and other communities of color need and deserve. Not only is such transformation vital to the well-being of U.S. democracy. It's vital to the freedom and wholeness of white people too"--